Basic influent sewage quality reflects sewershed characteristics in Tokyo city. (1st June 2022) - Guo, Zhongyu; Hatakeyama, Takayuki; Yoshimura, Chihiro; Wang, Tingting; Hatano, Yuta
Abstract: Sewage comprises multifarious information on sewershed characteristics. For instance, influent sewage quality parameters (ISQPs) (e.g., total nitrogen (TN)) are being monitored regularly at all treatment plants. However, the relationship between ISQPs and sewershed characteristics is rarely investigated. Therefore, this study statistically investigated relationships between ISQPs and sewershed characteristics, covering demographic, social, and economic properties in Tokyo city as an example of a megacity. To this end, we collected ISQPs and sewershed characteristic data from 2015 to 2020 in 10 sewersheds in Tokyo city. By principal component analysis, spatial variability of ISQPs was aggregated into two principal components (89.8% contribution in total), indicating organics/nutrients and inorganic salts, respectively. Concentrations of organics/nutrients were significantly correlated with the population in sewersheds (daytime population density, family size, age distribution, etc.). Inorganic salts are significantly correlated with land cover ratios. Finally, a multiple regression model was developed for estimating the concentration of TN based on sewershed characteristics ( R 2 =0.97). Scenario analysis using the regression model revealed that possible population movements in response to the coronavirus pandemic would substantially reduce the concentration of TN. These results indicate close relationships between ISQPs and sewershed characteristics and the potential applicability of big data of ISQPs to estimate sewershed characteristics and vice versa. HIGHLIGHTS: Influent sewage quality parameters (ISQPs) were classified into organics, nutrients, and inorganic salts. Organics and nutrients are mainly correlated to population information. Inorganic salts are significantly correlated to land-use characteristics. ISQPs concentration can be estimated by sewershed characteristics. Scenario analysis indicated total nitrogen concentration will decrease during/after COVID-19. Graphical Abstract